Improvement of Vascular Function by Knockdown of Salusin-β in Hypertensive Rats via Nitric Oxide and Reactive Oxygen Species Signaling Pathway - Pan, Yan; Sun, Shuo; Wang, Xingxing; Chen, Aidong; Fei, Xuejie; Wang, Wei; Han, Ying (Frontiers in Physiology, 2021)
Purpose: Salusin-β, a multifunctional vasoactive peptide, has a potentially important function in the pathological development of hypertension. However, the exact functional role of salusin-β and the underlying mechanism in this process are still not fully understood. The current study aimed to investigate the effects of silencing salusin-β on vascular function and vascular remodeling, as well as its signaling pathways in spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY). Methods: Silencing salusin-β was performed by caudal vein injection of adenovirus expressing salusin-β short hairpin RNA (shRNA). Acetylcholine (ACh)-induced endothelium-dependent relaxation was used to evaluate vasodilator function, and high K+ solution-induced constriction was used to evaluate vasoconstriction function. Results： Salusin-β levels in plasma and its protein expression in mesenteric artery (MA), coronary artery (CA), and pulmonary artery (PA) of SHR were higher than those in WKY. The salusin-β level and expression were decreased effectively by salusin-β shRNA. Knockdown of salusin-β decreased arterial blood pressure (ABP) and high K+ solution-induced vascular constrictions, and improved the endothelium-dependent relaxation and vascular remodeling in SHR. The improved effect of silencing salusin-β on ACh-induced relaxation in SHR was almost blocked by the nitric oxide synthase (NOS) inhibitor L-NAME. Compared to WKY, the endothelial NOS (eNOS) activity and level, and nitric oxide (NO) level were decreased, while NAD(P)H oxidase activity and reactive oxygen species (ROS) levels in MA, CA and PA of SHR were increased, which were all redressed by salusin-β knockdown. Conclusion: These results indicate that knockdown of salusin-β improves endothelium-dependent vascular relaxation and vascular remodeling, and decreases ABP and vasoconstriction in SHR, which might be accomplished by increasing eNOS activation and NO release while inhibiting NAD(P)H oxidase derived-ROS generation. Scavenging salusin-β improves vascular function and then prevents the development and progression of vasculopathy of hypertension.